The Role of Rewards in Improving Employee Performance at Favehotel Malang - Teronius Lipus; Gunawan, Cakti Indra; Moch. Nurhidayat (International Journal of Management and Business, 2025)
The purpose of this study was to determine the influence of the role of rewards in improving employee performance at FaveHotel Malang and to determine the impact of rewards on employee performance at FaveHotel Malang. This type of research is descriptive qualitative, the instrument uses interview guidelines, the informants used are 3 people (1 HRD and 2 employees), and the data analysis technique uses descriptive analysis. The results of the study show that the impact of giving rewards to employees at FaveHotel Malang is work enthusiasm, increased work motivation, employees working on time, and increased work discipline. The form of rewards given by FaveHotel Malang to employees, such as salary increases according to the UMR of Malang City, provision of Eid Allowances (THR), job promotions, and provision of rewards as a form of appreciation that the company shows to employees for their work motivation for the company. By giving rewards to employees so that they produce a greater contribution to the success of operations at Fave Hotel Malang, employees are also more motivated to pursue various types of rewards given by the company to employees, therefore employees are more inclined to try to work well to get rewards